Metagenomic insights into the modulatory effects of kelp powder (Thallus laminariae)-Treated dairy milk on growth performances and physiological lipometabolic processes of kunming mice - Xue, Fuguang; Mo, Qingnan; Ma, Pengyun; Zhang, Jian; Wang, Shuzhen; Zheng, Chuanxia; Sun, Yuqin; Liu, Minze; Yang, Zhengang; Bai, Hao (Frontiers in Nutrition, 2022)
Kelp powder, supplemented into dairy cow diet, effectively improved the milk polyunsaturated fatty acids (PUFAs) content. However, little information exists on the downstream effects of the kelp treated milk on body health, gut microbiota and nutrients metabolism. For this purpose, 48 three-week old Kunming (KM) male mice with the average body weight of 16.1g ± 0.2g were randomly divided into the control treatment (CON, fed with standard chow), the common milk supplement treatment (Milk), and the kelp powder treated milk supplement treatment (KPM). Experiment lasted for 35 days, with a 7-days long adaptive period and a 28-days long main trial. Phenotypic parameters included growth performances and serum lipids related parameters were first measured, results indicated that Milk and KPM supplement significantly promoted the total body weight gain (P<0.05), while significantly decreased the feed conversion ratio compared with CON (P<0.05). No significant differences were observed on the blood lipids content among all three treatments, however, the triglyceride content showed a decreasing trend after KPM supplement treatment. Further, activities of liver lipometabolic related enzymes were investigated to determine the underlying factors that impacted physiological lipid metabolism. KPM treatment showed a significant reductive effects on the activity of lipogenesis-related enzymes such as FAS and ACC, while a significant stimulative effects on the activity of lipolysis-related enzymes included the ATGL and CPT1 compared with CON (P<0.05). Finally, gastrointestinal tract development and cecal microbiota community that correlated with body lipid degradation and absorption were measured to determine the underlying mechanism of KPM supplementation on physiological lipid metabolism. Results indicated that supplemented with KPM significantly enhanced cecal bacteria diversity which was reflected in the significant increase of Chao1 and ACE indexes. Besides, starch-degraded bacteria such as Faecalibacterium, Ruminococcaceae, and Streptococcus are significant decreased (P<0.05), while cellulose-degraded bacteria included Parabacteroides, Prevotella, Lactobacillus, Clostridium and Bifidobacterium are significant increased (P<0.05) after KPM supplement, which may further restrict the energy generation and therefore reduced the lipid deposition. In summary, kelp supplement help increased the milk PUFAs content, enhanced the bacterial diversity and relative abundances of probiotics, which finally modulated physiological lipid metabolism and promoted the growth performances.